German immigrants in America : an interactive history adventure - Raum, Elizabeth (You choose books, 2008)
Describes the experiences of German immigrants upon arriving in America, revealing historical details from the perspective of Germans who came to Texas in the 1840s, the Dakota Territory in the 1880s, and Wisconsin before the start of World War I.